2008
DOI: 10.3998/ark.5550190.0009.f21
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and reactions of p-hydroxythiobenzamides

Abstract: Ethoxycarbonyl isothiocyanate reacted with phenols in a nitromethane solution of aluminum chloride to yield the appropriate 4-hydroxy-N-ethoxycarbonylthiobenzamides. In the reaction with dinucleophiles they gave heterocyclic compounds which were subsequently functionalized on the hydroxy group. The reaction of p-hydroxythiobenzamides with carbamoyl chloride, chlorides of α,β-unsaturated carboxylic acids, and isocyanates yielded the corresponding O-acylated products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…A Friedel-Cras-type reaction of organic isothiocyanates with aromatic compounds is a straightforward synthetic route to secondary thioamides. [28][29][30][31] We recently reported that a reaction of pyrene with ethoxycarbonylisothiocyanate afforded Nethoxycarbonyl-pyrene-1-carbothioamide in 95% yield. 32 Primary thioamides were obtained in a reaction of electron-rich arenes (1,2-diethoxybenzene, ferrocene) with potassium thiocyanate in methanesulfonic acid.…”
Section: Resultsmentioning
confidence: 99%
“…A Friedel-Cras-type reaction of organic isothiocyanates with aromatic compounds is a straightforward synthetic route to secondary thioamides. [28][29][30][31] We recently reported that a reaction of pyrene with ethoxycarbonylisothiocyanate afforded Nethoxycarbonyl-pyrene-1-carbothioamide in 95% yield. 32 Primary thioamides were obtained in a reaction of electron-rich arenes (1,2-diethoxybenzene, ferrocene) with potassium thiocyanate in methanesulfonic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Thioamides and their derivatives are useful synthons in organic synthesis, such as in regio- and stereoselective heterocyclization reactions . Moreover, they can be used as flotation and vulcanization agents, as additives to lubricating oils and greases and as interesting ligands in coordination chemistry .…”
Section: Introductionmentioning
confidence: 99%
“…Thioamides and their derivatives are useful synthons in organic synthesis, 12 such as in regio-and stereoselective heterocyclization reactions. 13 Moreover, they can be used as flotation 14 and vulcanization agents, 15 as additives to lubricating oils and greases 16 and as interesting ligands in coordination chemistry. 17 Thioamides are often prepared via the reaction of isothiocyanates with aromatic compounds catalyzed by Lewis acids 18 (Scheme 2A), thioacylation of amines with thioformates, 19 dimethyl thioformamide, 20 or carbon mono 21 or disulfide 22 (Scheme 2B), formal oxygen−sulfur replacement on oxoamides in the presence of thionating agents including the Lawesson reagent, 23 phosphorus pentasulfide, 24 or elemental sulfur 25 (Scheme 2B), partial reduction of isothiocyanates with reducing agents (Scheme 2C), 26 and Schwartz reagent (Scheme 2,D).…”
Section: ■ Introductionmentioning
confidence: 99%
“…High reactivity of the thioamide group towards both electro-and nucleophilic agents, often in conjunction with that of other reactive centers in the molecule, made thioamides handy building blocks of particular importance in the synthesis of heterocyclic systems by inter-and intramolecular cyclization. [1][2][3][4][5] Saturated or partially saturated heterocyclic compounds with a thioamide group were found to be of interest as potential ionic liquid media. 6 Bogdanowicz-Szwed and co-workers reported the base-catalyzed reaction of β-ketothioamides with (E)-β-nitrostyrenes which yielded spiro(indane-1,3′-thiophenes).…”
Section: Introductionmentioning
confidence: 99%